Role Conceptions of Brussels Correspondents from the New Member States - Lecheler, Sophie K.; Hinrichsen, Malte C. (Javnost-The Public, 2010)
Journalists working in Brussels are commonly perceived as different from traditional foreign correspondents. However, their isolation from their home offices also renders them distinct from domestic political journalists. Consequently, studies of Brussels correspondents have come up with their own viable types of “political journalism in Brussels.” With the ongoing enlargement of the European Union – and a growing number of post-communist new member states – we need to re-define current typologies of Brussels journalism. Prior findings indicate that post-communist journalists have not yet evolved a fixed set of professional roles, norms and values. Thus, their work in Brussels may be characterised by a different approach towards correspondent journalism. As part of a study on Brussels correspondents, role conceptions of correspondents from post-communist new member states were examined. In-depth, semi-structured interviews with 14 journalists from different new member states show that explicative, objective and rapid information-gathering are the most important constituents of political journalism in Brussels. As a consequence of the highly-complex subject matter of EU reporting and declining support from home offices, journalists see it as their highest goal to explain the EU and make the EU decision-making process in Brussels better understood. Along this line, other forms of political journalism, such as investigative and critical reporting, are neglected.